2021
DOI: 10.1002/2211-5463.13270
|View full text |Cite
|
Sign up to set email alerts
|

ZIPK activates the IL‐6/STAT3 signaling pathway and promotes cisplatin resistance in gastric cancer cells

Abstract: Gastric cancer is one of the most common malignant cancers globally. Chemotherapy resistance remains a major obstacle in the treatment of gastric cancer, and the molecular mechanisms underlying drug resistance are still not well understood. We previously reported that Zipper interacting protein kinase (ZIPK), also known as death‐associated protein kinase3, exerts an oncogenic effect on gastric cancer via activation of Akt/NF‐κB signaling and promotion of stemness. Here, we explored the roles of ZIPK in cisplat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Altogether, these findings suggest that tumor suppression by DAPK3 in GC is associated with autophagy. Recent studies revealed that DAPK3 may act on cisplatin resistance in GC cells by activating the IL-6/STAT3 signaling pathway . In NSCLC, the upregulation of Vir-Like m6A methyltransferase associated (VIRMA) promotes the N 6 -methyladenosine (m6A) modification of DAPK3, and the downregulation of DAPK3 contributes to the progression of NSCLC .…”
Section: The Dapk Family In Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Altogether, these findings suggest that tumor suppression by DAPK3 in GC is associated with autophagy. Recent studies revealed that DAPK3 may act on cisplatin resistance in GC cells by activating the IL-6/STAT3 signaling pathway . In NSCLC, the upregulation of Vir-Like m6A methyltransferase associated (VIRMA) promotes the N 6 -methyladenosine (m6A) modification of DAPK3, and the downregulation of DAPK3 contributes to the progression of NSCLC .…”
Section: The Dapk Family In Diseasesmentioning
confidence: 99%
“…Recent studies revealed that DAPK3 may act on cisplatin resistance in GC cells by activating the IL-6/STAT3 signaling pathway. 152 In NSCLC, the upregulation of Vir-Like m6A methyltransferase associated (VIRMA) promotes the N 6methyladenosine (m6A) modification of DAPK3, and the downregulation of DAPK3 contributes to the progression of NSCLC. 153 In addition, DAPK3 knockdown inhibits cell proliferation, migration, and invasion through ERK/c-myc signaling in A549 cell lines, suggesting that DAPK3 is a promising target for the treatment of NSCLC 154 (Table 3).…”
Section: Dapk1 In Diseasesmentioning
confidence: 99%